Design of a Web-based Air Conditioner Monitoring and Control System - Moch. Rizki Maulana (Indonesian Journal of Engineering and Technology (INAJET), 2023)
Air Conditioner (AC) is an electronic device that has a function to control the temperature in a room. The use of air conditioners on a household scale is intended so that users can easily control the room temperature so that it stays cool and comfortable. However, the limitations in controlling the AC remotely make it less than optimal. So a web-based AC monitoring and control system was designed which aims to make it easier for users to remotely control the AC via the web which can be accessed using a smartphone or laptop as long as it is connected to an internet connection. This system utilizes the NodeMCU ESP8266 microcontroller to be able to access the WiFi network in order to gain internet access and uses several supporting sensors such as DHT11 temperature and humidity sensors, PZEM-004T sensors, and several supporting components.